Climate change impacts and product lines - Szentteleki, K.; Ladányi, M.; Gaál, M.; Hegedűs, A. (International Journal of Horticultural Science, 2010)
This paper summarizes the main effects of extreme weather events on agricultural production and demonstrates their economic consequences. For cost-benefit analysis of economic impacts and for determination of risk levels simulation models are needed that contains the relationship between product line levels and elements. WIN-SIM model is developed for this goal, specialized for wine production. The model is suitable to analyze the market share, the cost and income relations as well as the relation structure of the product lines. The four levels of the model (site, vine growing, wine production and wine market levels) have individual values added from the aspect of end product, where the product line sets out from the site level and gets through the levels up to the consumer segments. Theoretically, all elements can be connected to any element of the next level and sublevel, but there are “prohibited contacts” because of professional, regulation or production practice reasons.